Mixing of rubber compounds - Limper, A. (Hanser Publishers ; Hanser Publications, 2012)
The book covers the major aspects of rubber compounding. For the first time, the reader will find all relevant issues, whether it is machine design, process technology, or material parameters, covered in one comprehensive volume.
Keywords: Rubber.; Rubber machinery.; Mixing machinery.; elektronické knihy; electronic books